Antiulcerogenic Effects and Possible Mechanism of Action of Quassia Amara (L. Simaroubaceae) Extract and Its Bioactive Principles in Rats - Raji, Yinusa (African Networks on Ethnomedicines, 2011)
The effects of Quassia amara extract (Q. amara) and its bioactive principles-quassin and 2-methoxycanthin-6-one on gastric ulceration were studied in albino rats. Q. amara (200–800 mg/kg p.o.; 5–20 mg/kg i.p) and 2-methoxycanthin-6-one (12.5, 25.0 and 50.0 mg/kg p.o; 1, 2 and 4 mg/kg i.p) but not quassin (12.5, 25.0 and 50 mg/kg p.o; 1, 2 and 4 mg/kg i.p) significantly inhibited gastric ulceration induced by indomethacin (40mg/kg). Administration of Q. amara (800 mg/kg p.o and 20 mg/kg i.p) and 2-methoxycanthin-6-one (12.5 mg/kg p.o; 4 mg/kg i.p) caused between 77%–85% cytoprotection against indomethacin (40 mg/kg, i.p) — induced gastric ulceration. Quassin did not cause any significant change in indomethacin-induced gastric ulceration. The inhibition of gastric ulceration produced by Q. amara and 2-methoxycanthin-6 one was accompanied by significant dose-dependent decreases (P< 0.01) in total gastric acidity. To investigate the probable mechanism of action, the individual effects of the extract and its principles alone and in combination with histamine (1 mg/kg) or cimetidine (0.12 mg/kg) on gastric acid secretion in situ were studied. Q. amara (20 mg/kg) and 2-methoxycanthin-6-one (4 mg/kg) but not quassin significantly (P< 0.01) inhibited the basal and histamine-induced gastric acid secretion. Inhibition of gastric acid secretion by Q. amara and 2-methoxycanthin-6-one was accentuated by cimetidine. The results suggest that Q. amara and its bioactive principle, 2-methoxycanthin-6-one possess antiulcer activity probably acting via histamine H(2) receptor. This could be a potential source of potent and effective antiulcer agents.